2018
DOI: 10.14393/bj-v34n1a2018-37842
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ecological water quality along a rural to urban land use gradient using benthic macroinvertebrate-based indexes

Abstract: Agricultural practices such as livestock grazing and tilling can result in soil erosion and runoff of fine sediments, nutrients (e.g. nitrogen, phosphorus, potassium) and pesticides, leading to degradation of aquatic environments. Urbanization is also responsible for a variety of impacts on fluvial ecosystems, including pollution by heavy metals, oil, domestic sewage and garbage. In this study, we evaluate the impact of land use on stream health of the Uberabinha river catchment. Overall, rural streams present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
1
7
1
2
Order By: Relevance
“…For example, while previous findings in the lowland Swiss Mönchaltorfer Aa catchment showed that EPT richness was highest in least impacted sites mostly upstream of urban and agricultural areas, our greatest EPT richness was along sites IMC4 and IMC5, which are in wellforested reaches downstream of the agricultural areas but within the urban zone (Baumgartner and Robinson 2017). Also, contrary to findings from Brazil's Uberabinha river catchment and Chile's Mediterranean ecoregion, we did not find urban reaches to have less richness or diversity of sensitive taxa than agricultural reaches in the Indian Mill Creek watershed (Nascimento et al 2018;Fierro et al 2019). This divergence from other catchments suggests that one possible reason for this increase in EPT richness is that there is a forested section of the middle Indian Mill Creek watershed within the urban zone, which provides habitats and shelter for aquatic organisms (Fig.…”
Section: Locations Of Greatest Impactscontrasting
confidence: 99%
See 2 more Smart Citations
“…For example, while previous findings in the lowland Swiss Mönchaltorfer Aa catchment showed that EPT richness was highest in least impacted sites mostly upstream of urban and agricultural areas, our greatest EPT richness was along sites IMC4 and IMC5, which are in wellforested reaches downstream of the agricultural areas but within the urban zone (Baumgartner and Robinson 2017). Also, contrary to findings from Brazil's Uberabinha river catchment and Chile's Mediterranean ecoregion, we did not find urban reaches to have less richness or diversity of sensitive taxa than agricultural reaches in the Indian Mill Creek watershed (Nascimento et al 2018;Fierro et al 2019). This divergence from other catchments suggests that one possible reason for this increase in EPT richness is that there is a forested section of the middle Indian Mill Creek watershed within the urban zone, which provides habitats and shelter for aquatic organisms (Fig.…”
Section: Locations Of Greatest Impactscontrasting
confidence: 99%
“…The feeding guilds and other traits of stream organisms can also reflect environmental variables (Usseglio- Polatera et al 2000;Merritt et al 2006). The composition of aquatic communities can be vastly different depending on the land use surrounding streams, for instance urban and agricultural areas (Nascimento et al 2018), as well as longitudinally (Vannote et al 1980). Low-agriculture areas with extensive vegetation buffers may support the greatest biological integrity for aquatic communities because of the habitats there, such as pools and woody debris (Effert-Fanta et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioindicators of environmental impact based on benthic macroinvertebrates gained special relevance in Europe (Dermott and Pachkevitch, 2012). However, in Chile and South America they are mostly used to assess the ecological condition of rivers (Brand and Miserendino, 2015;Cardoso and Novaes, 2013;Correa-Araneda, 2016;Correa-Araneda et al, 2010;Dedieu et al, 2016;Dos Santos, 2017;Fierro et al, 2016;Figueroa et al, 2003;Kay et al, 2001;Lallement et al, 2014;Luo et al, 2018;Meza-S et al, 2012;Miserendino et al, 2012;Nascimento et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Os ecossistemas aquáticos são formados por interações complexas entre fatores bióticos e abióticos e estes têm sofrido alterações significativas como resultado das intensas atividades antrópicas, como lançamento de efluentes domésticos e industriais não tratados, desmatamento, atividades agrícolas, construção de barragens e represas, entre várias outras atividades (Goulart & Callisto 2003, Nascimento et al 2018. Entre as principais alterações que ocorrem nesses ecossistemas, Callisto et al (2005) ressaltam a redução da biodiversidade aquática como consequência da desestruturação do ambiente físico, químico e biológico, resultando em perda de qualidade e dificuldade na manutenção da integridade ambiental desses ecossistemas aquáticos.…”
Section: Introductionunclassified